DETERMINANTS OF TECHNICAL EFFICIENCY OF THE BANKS LISTED ON THE VIETNAMESE STOCK EXCHANGE - Duy, Vuong Quoc (International Journal For Research In Business, Management And Accounting, 2018)
This paper investigates the efficiency of commercial banks listed on the Vietnamese Stock Exchange by using the methods of qualitation and quantitation. This qualitative analysis base on some financal indexs and is combined with the quantitative analysis by Data Enverlopment Analysis (DEA) and Tobit model. This panel data set consists of 38 banks with 114 observations for the period 2013-2015. There are three input variables such as deposit, fixed assets and labor costs and two output variables including return on interest and return out interest. Finally, the finding showed that the average technical efficency of 38 banks is 0,861 and efficency of cooperational commercial banks is higher efficency of state banks. The factors that impact on efficency of banks are rate of fixed assets and labor costs, rate of deposits and loans, rate of return on interest and revenues.